SALURAN PEMASARAN JAGUNG PADA PROGRAM TANAM JAGUNG PANEN SAPI (TJPS) DI DESA ANAENGGE, KECAMATAN KODI, KABUPATEN SUMBA BARAT DAYA - Lado, Hendrikus Umbu; Nendissa, Doppy Roy; Pellokila, Marthen R. (Buletin Ilmiah Impas, 2024)
Corn marketing channels help farmers to convey persuasive messages to consumers to buy corn. Marketing channels help estimate the amount of demand for corn, making it easier for farmers to prepare corn orders.This research aims to determine the corn marketing channels in the research area, the magnitude of corn marketing costs in the research area, the share margin of corn marketing channels in the research area, and the efficiency of corn marketing in the research area. The research location was purposively selected in Anaengge Village, Kodi Sub-district, Southwest Sumba District. This village was chosen because it is one of the areas that produces corn in Southwest Sumba District. The research took place from June to August 2023. The results of the research show that the marketing channels in the research area consist of two channels. The first marketing channel goes from farmers to collecting traders and then to the factory. The second marketing channel goes from farmers to small agent traders, then to collecting traders (large agents), and finally to the factory. The marketing cost in Channel I is Rp. 176, which includes transportation, labor, ropes, and drying costs for the collecting trader (large agent). In Channel II, the marketing cost is Rp. 249, which includes transportation, drying, labor, and ropes. The share margin obtained in Channel I is 90.9% with a marketing cost of Rp. 5,176/kg. The share margin obtained in Channel II is 83.33% with a marketing cost of Rp. 5,219/kg. The efficiency value of Channel I is 3.21%, falling into the category of 0-33%, which means that Channel I is an efficient marketing channel. The efficiency value of Channel II is 4.15%, also falling into the category of 0-33%, indicating that Channel II is an efficient marketing channel.